Lateral Subtalar Dislocation with Tarsometatarsal Dislocation: A Case Report of a Rare Injury - Samik Banerjee; Mostafa M. Abousayed; Douglas J. Vanderbrook; Kaushik Bagchi (Case Reports in Orthopedics)
Dislocation of the fourth and fifth tarsometatarsal joints in conjunction with lateral subtalar dislocation is a rare occurrence. Little is known about the mechanism of injury, the appropriate treatment for this condition, and its ultimate prognosis. In this report, we describe this atypical presentation in a middle aged, otherwise healthy male who sustained a trivial twisting injury to the ankle when he slipped and fell on ice. Open reduction and K-wire fixation were necessary to affix the lateral tarsometatarsal and talonavicular joints. At one year postoperatively, he was able to return to his preinjury occupation with mild to moderate pain with prolonged walking. His Foot and Ankle Disability Index and American Orthopaedic Foot and Ankle Society scores were 64 and 65 points, respectively. Surgical intervention resulted in a stable plantigrade foot; however, the patient had early radiographic evidence of posttraumatic arthritis in the midfoot joints at one-year follow-up.